DETEKSI KEMIRIPAN SOURCE CODE DENGAN METODE FINGERPRINT BASED DISTANCE DAN LEVENSHTEIN DISTANCE - Jimmy Jimmy; Viny Christanti Mawardi; Agus Budi Dharmawan (Computatio : Journal of Computer Science and Information Systems, 2018)
The ease of accessing information makes easier to do plagiarism. Plagiarism not only applied to written essay, but these day copying other people’s program is also considered as plagiarism. This paper will researching an method to automatically calculating the similarity of pair of source code. The method used are fingerprint based distance and Levenshtein Distance. The result will be measured in accuracy, precision, and recall. The result is in some dataset, levenshtein distance is better than fingerprint based distance for detecting plagiarism in student’s code especially beginner in C++.